2022
DOI: 10.1128/aac.02125-21
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Pharmacokinetics and Safety of Intravenous RTD-1

Abstract: Severe illness caused by Coronavirus disease 2019 (COVID-19) is characterized by an overexuberant inflammatory response resulting in acute respiratory distress syndrome (ARDS) and progressive respiratory failure (1). Rhesus theta (θ) defensin-1 (RTD-1) is a macrocyclic host defense peptide exhibiting antimicrobial and immunomodulatory activities. RTD-1 treatment significantly improved survival in murine models of a severe acute respiratory syndrome (SARS-CoV-1) and endotoxin-induced acute lung injury (ALI) (2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…These values are comparable to those obtained by [17]. Park et al [14] found that the pH of marinated pork was likewise shown to be somewhat acidic. The pork belly was marinated in various concentrations of green tea and yerba mate.…”
Section: Physicochemical Properties Phsupporting
confidence: 88%
See 1 more Smart Citation
“…These values are comparable to those obtained by [17]. Park et al [14] found that the pH of marinated pork was likewise shown to be somewhat acidic. The pork belly was marinated in various concentrations of green tea and yerba mate.…”
Section: Physicochemical Properties Phsupporting
confidence: 88%
“…Additionally, ready-to-eat foods may benefit from the application of turmeric extracts as natural preservatives [13]. In fortified beverages and milk as colloidal food models, the usage of turmeric extract has also been investigated as nanopolisomes and nanoemulsions loaded, which act as antioxidants and antimicrobials [14]. Nowadays, various studies have concentrated on creating and analyzing edible films that include curcumin as a bioactive substance because of its antibacterial and antioxidant qualities [15].…”
Section: Introductionmentioning
confidence: 99%
“…The cyclopeptide RTD-1, which has anti-SARS-CoV effects, was found to be safe to support its investigation for treatment of COVID-19. 530 …”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 99%
“…To the best of our knowledge, there are no selective ADAM10-targeted RA therapies on the market or in development. RTD-1, a macrocyclic peptide inhibitor of ADAM17, is currently being evaluated by Oryn Therapeutics [ 15 , 16 , 17 ]. Disease-modifying small molecule anti-rheumatic drugs (DMARDs) approved or under evaluation for therapy in RA include Janus kinase (JAK) inhibitors, TNF inhibitors, T cell co-stimulation blockers, IL-6 receptor inhibitors, promoters of B cell depletion, and interleukin 1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%